1983
DOI: 10.1113/jphysiol.1983.sp014963
|View full text |Cite
|
Sign up to set email alerts
|

Response to the length of moving visual stimuli of the brisk classes of ganglion cells in the cat retina.

Abstract: Response histograms were collected for brisk-sustained and brisk-transient ganglion cells in the cat retina as narrow bars were moved backwards and forwards across their receptive fields. When a bar of fixed length was moved across the centre of the receptive field with contrast proportional to velocity, a constant response was obtained as long as the centre of the receptive field was crossed within the summation time. However, if the length of the bar was such that it extended beyond the centre, then there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The biases seen in the present study of feline dLGN cells were found in X and Y cells, and cells exhibiting such biases did not appear to differ in any other respect from those with no bias. Although previous reports have not identified directional biases in feline retinal ganglion cells, only a very small number of studies have used similar stimulus protocols to those used in the present study (Rodieck & Stone, 1965;Lee & Willshaw, 1978;Cleland, Harding & Tulanay-Keesey, 1983a). Given that these previous studies primarily addressed other issues, it would appear premature to disregard the possibility that such biases might occur in the retina.…”
Section: Cells With Directional Biasmentioning
confidence: 85%
“…The biases seen in the present study of feline dLGN cells were found in X and Y cells, and cells exhibiting such biases did not appear to differ in any other respect from those with no bias. Although previous reports have not identified directional biases in feline retinal ganglion cells, only a very small number of studies have used similar stimulus protocols to those used in the present study (Rodieck & Stone, 1965;Lee & Willshaw, 1978;Cleland, Harding & Tulanay-Keesey, 1983a). Given that these previous studies primarily addressed other issues, it would appear premature to disregard the possibility that such biases might occur in the retina.…”
Section: Cells With Directional Biasmentioning
confidence: 85%
“…The possible sources include the following: (1) mechanisms of suppression or gain control operating in retina (Cleland et al, 1983b; Responses were aligned so that maximum receptive field response is centered on 0°. Kaplan et al, 1987;Sclar, 1987;Cheng et al, 1995;Girardin et al, 2002;Nolt et al, 2004); (2) inhibitory circuitry in thalamus (Hubel and Wiesel, 1961;McIlwain and Creutzfeldt, 1967;Singer and Creutzfeldt, 1970;Levick et al, 1972;Cleland et al, 1983b;Cleland and Lee, 1985;Sherman and Koch, 1986;Kaplan et al, 1987;Funke and Eysel, 1998); and (3) negative feedback from visual cortex (Ahlsén and Lindström, 1983;Sherman and Koch, 1986;Murphy and Sillito, 1987;Sillito et al, 1993;Cudeiro and Sillito, 1996;Sillito and Jones, 2002;Webb et al, 2002;Worgotter et al, 2002;Alitto and Usrey, 2003).…”
Section: Origins Of the Suppressive Fieldmentioning
confidence: 99%
“…The luminance of the spot without filters was 100 cd/M2 and this was reduced by interposing suitable neutral density filters. Contrast was defined as 'luminance of spot above background/luminance of background' (Cleland, Harding & Tulunay-Keesey, 1983). The luminances of spot and background were monitored regularly.…”
Section: Discrimination Offast Motionmentioning
confidence: 99%